Na2SO4·10H2O dehydration in view of thermal storage. (29th September 2015) - Donkers, P.A.J.; Linnow, K.; Pel, L.; Steiger, M.; Adan, O.C.G.
Abstract: The idea of using hydrated salts as working media for thermal energy storage has increased the interest in understanding their phase transitions. During studying the phase transition of mirabilite into thenardite, the crystal structure and water content are monitored by three experimental techniques. With the help of NMR, homogeneous drying of mirabilite crystals over the entire grain is observed. According to the drying behavior, the mobility of water molecules should be high inside the grain during dehydration. XRD experiments show that during this phase transition no disordered phase or other metastable phases like Na2 SO4 ·7H2 O or phase III appear. With Raman spectroscopy, these experiments are repeated at several relative humidities and again no metastable phases are observed. Abstract : Graphical abstract: Abstract : Highlights: We studied the dehydration of mirabilite with help of NMR, XRD and Raman. The phase transformation from mirabilite into thenardite is observed to be a one-to-one process. No metastable crystal phases are observed by XRD and Raman during the dehydration process. A homogeneous drying process inside the grain is observed.